2004
DOI: 10.1111/j.1067-1927.2004.12608.x
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to improve angiogenesis in tissue‐engineered skin

Abstract: A problem with tissue-engineered skin is clinical failure due to delays in vascularization. The aim of this study was to explore a number of simple strategies to improve angiogenesis/vascularization using a tissue-engineered model of skin to which small vessel human dermal microvascular endothelial cells were added. For the majority of these studies, a modified Guirguis chamber was used, which allowed the investigation of several variables within the same experiment using the same human dermis; cell type, angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 20 publications
0
28
1
Order By: Relevance
“…4,5 This method does not depend on an autologous cell source, but the slow growth of new vessels may compromise tissue viability. 6 Alternatively, one can seed vascular endothelial cells into the implanted tissue as a means of accelerating vessel formation. [7][8][9][10][11] This method relies on vasculogenesis in situ, and the time it takes for this process to occur may, again, compromise the implanted tissue.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 This method does not depend on an autologous cell source, but the slow growth of new vessels may compromise tissue viability. 6 Alternatively, one can seed vascular endothelial cells into the implanted tissue as a means of accelerating vessel formation. [7][8][9][10][11] This method relies on vasculogenesis in situ, and the time it takes for this process to occur may, again, compromise the implanted tissue.…”
Section: Introductionmentioning
confidence: 99%
“…These results have highlighted the importance of the reepithelialization process to achieve a functional trachea substitute [3][4][5]. The experience gained from tissue-engineered skin demonstrated that epithelial cells have better survival chances on a well-vascularized wound surface [6,7], a clear proof that revascularization is the essence of reepithelialization.…”
Section: Introductionmentioning
confidence: 92%
“…These results were not surprising at all, since the entire history of trachea replacement has highlighted the importance of a complete reepithelialization process in building a functional tracheal substitute. The experience gained from tissueengineered skin demonstrated that epithelial cells have better survival chances on a well vascularized wound surface, a clear proof that revascularization is the essence of reepithelialization [41][42][43][44].…”
Section: Problems Faced: Reepithelialization and Revascularizationmentioning
confidence: 99%